TINJAUAN YURIDIS PEMBAGIAN WARIS BAGI AHLI WARIS YANG BERBEDA AGAMA DENGAN PEWARIS DITINJAU DARI HUKUM ISLAM DAN HUKUM PERDATA - Bistamam '; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Which one explanation in inheritance law is explanation about someone who is rightful to receive inheritance and someone who is hindered to receive inheritance. The cause of someone receive inheritance is relationship marriage, kinship and freeing slaves. While someone hindered to receive inheritance which one it who is diference religion between the heir and the heirs can to miscarry someone fo rightful to inherit it inheritance. The purpose of this thesis are: first, to khow how division of inheritance for the heirs a diference religion with the heir in review of civil law and islamic law. Second, to know how judgement of judge in decide case for the heirs a diference religion with the heir.The type of research are used in author this in research is a normative legal research. This research discuss the comparative law. The source of data used are secondary data obtained from the literature another the official document, books, research of the result are tangible report and so forth.The conclusion that can obtained from this research the first, division of heritance for hers different religion the heir in term of islamic law is a barrier or heiirs to get inheritance. This matter reiforced with Hadits Rasulullah SAW which mean “Moslem people can not inheritance freasure moslem people. In article 171 alphabet c compilation of islamic law also clarify about heirs different religion with heir a barrier to get inheritance. While in terms of civil law, not article which govern expressly about heirs different religiion with heir. In article 382 civil law stated that entitled to be heirs is the nearest relation both legitimate nor outdoor wedding and husband who live longest. Second, to decide case, judge obligatory give judgement of law and sense of justice. As the verdict number 16/AG/2010. Judge have consideration that marriage heir with heirs long enough that is 18 years means long enough heirs devoted on heir and case heirs with heir while alive mingle harmonisously peace although different religion, therefore worth and worthy heirs obtaining inheritance heir the form testament wajibah.Keywords: Inheritance-Heirs-Difference Religion